Synthesis and Characterization of a Molecularly Imprinted Polymer for Methylene Blue - Asman, Saliza; Azah Yusof, Nor; Halim Abdullah, Abdul; Jelas Haron, Md. (Asian Journal of Chemistry, 2011)
This study reports the preparation of a molecularly imprinted polymer for the removal of methylene blue dye from aqueous media. The methylene blue-molecularly imprinted polymer was prepared using bulk polymerization via radical polymerization containing methylene blue as a template, methacrylic acid, as a monomer, ethylene glycol dimethacrylate as a cross-linker, benzoyl peroxide as an initiator and tetrahydrofuran as a solvent (porogen) in ratios of 0.117 mmol, 0.930 mmol, 4.650 mmol, 10.000 mg and 30.000 mL, respectively. The polymer block obtained was ground and sieved using a 90 μm sieve and the methylene blue template was removed from the methylene blue-molecularly imprinted polymer by extracting it with methanol/ acetic acid/water (8:1:1) mixture. The non-molecularly imprinted polymer was synthesized as a reference. The methylene blue-molecularly imprinted polymer was characterized by using Fourier-transform infrared spectroscopy, scanning electron microscopy, a particle size analyzer and BET equation. The effect of different parameters such as pH, time and concentration of methylene blue, selectivity and reusability of the methylene blue-molecularly imprinted polymer were evaluated. Maximum sorption of methylene blue occurred at pH 5 in 30 s. The sorption followed a pseudo-second-order kinetic model. The adsorption isotherm of methylene blue followed the Freundlich isotherm model. The selectivity study had proved that the methylene blue-molecularly imprinted polymer was highly selective to the methylene blue analyte.